The scale of the central beach change processes in the west coast of Nha Trang bay - Huu, Vu Cong; Uu, Dinh Van (Vietnam Journal of Marine Science and Technology, 2020)
The central beach in west coast of Nha Trang bay has experienced erosion in recent years. The determination of hydrodynamic regime and causes of this beach fluctuation is still an open problem and is concerned by scientists and managers. This study shows the causes and scales of the shoreline change processes based on the results of shoreline change model and the analysis of remote sensing images of shoreline location.